Weaknesses of Strict Liability Regulations in Environmental Crimes And Their Implications for the Effectiveness of Environmental Law Enforcement in Indonesia - I Made Juni Artawan; Faisal Santiago (Ridwan Institute, 2026)
Environmental crimes have become a significant challenge to achieving sustainable development due to increasing industrial activities, natural resource exploitation, and environmental pollution. In Indonesia, environmental law enforcement continues to face substantial obstacles, particularly in addressing cases involving corporations and high-risk activities. Although the strict liability principle regulated under Article 88 of Law Number 32 of 2009 concerning Environmental Protection and Management is intended to strengthen accountability without requiring proof of fault, its implementation remains limited because environmental criminal provisions continue to emphasize fault-based liability under Articles 98 and 99. This study aimed to examine the weaknesses of strict liability regulations in environmental crimes and analyze their implications for the effectiveness of environmental law enforcement in Indonesia. This research employed a normative juridical method using statutory and analytical approaches by examining relevant legal provisions, legal doctrines, scientific literature, and environmental law regulations. The findings indicated that the main weaknesses of strict liability regulations included the lack of integration between strict liability provisions and environmental criminal liability mechanisms, uncertainty regarding their application in criminal proceedings, and limitations in imposing accountability on corporations for environmental damage. These weaknesses have created challenges in evidentiary processes and reduced the effectiveness of environmental law enforcement. This study concluded that regulatory reform was required to systematically integrate strict liability principles into environmental criminal law mechanisms to strengthen legal certainty, enhance corporate accountability, and promote sustainable environmental protection in Indonesia.